Restriction endonuclease EcaI from Enterobacter cloacae - Hobom, G. (1981)
Restriction endonuclease EcaI obtained from Enterobacter cloacae DSM30056 recognizes the group of heptanucleotide palindromes 5′-G[unk]G-T-N-A-C-C-3′, and on cleavage (arrow) produces fragments with 5′-terminal pentanucleotide extensions. It is identical in specificity with restriction endonuclease BstEII from Bacillus stearothermophilus ET.